Diversity and characterization of Citrus tristeza virus and Candidatus Liberibacter asiaticus associated with citrus decline in major citrus growing areas of India - DIPAK KUMAR GHOSH (LKN), PRADEEP KUMAR SHUKLA and DILIP KUMAR GHOSH*, ASHISH WARGHANE, PRAGATI MISRA (Indian Phytopathology, 2017)
Tristeza and Citrus greening disease (Huanglongbing, HLB) are two most destructive diseases of citrus worldwide. Tristeza disease is caused by Citrus tristeza virus (CTV), a phloem limited, monopartite, and single-stranded RNA virus whereas citrus greening disease is induced by three different species of a Gram negative, non-cultured, alpha proteobacteria ‘Candidatus Liberibacter'. Among the three species, ‘Candidatus Liberibacter asiaticus’ is most devastating and widely distributed pathogen in Indian subcontinent. In the present study, thirty leaf and twig samples were collected during 2013-16 from citrus plants showing moderate to severe decline symptoms in field from three different states viz., Maharashtra, Assam and West Bengal that are considered as important citrus growing belts of India. Molecular diagnosis by PCR (Polymerase chain reaction) using pathogen specific primers shows that out of thirty samples tested, twenty one samples were found positive with CTV, seventeen samples were infected with ‘Ca. L. asiaticus’ and ten samples were mix infected with both the pathogens while two tested negative. Sequences of coat protein gene (CPG) of CTV isolates showed 97% to 100% sequence identity with CTV sequences available in the GenBank. In phylogenetic analysis, all sequenced CTV isolates were grouped into five clades indicating the presence of at least five different CTV strains that are associated with declined citrus trees of Maharashtra, Assam and West Bengal. Similarly, nucleotide sequence of 16S rRNA gene of ‘Ca. L. asiaticus’ shows 97% to 100% identity with sequences of other reported isolates. Phylogenetic analysis of the 16S rRNA gene indicated that HLB isolates associated with citrus decline in the present study belong to ‘Ca. L. asiaticus’ species. A robust and sensitive duplex PCR has also been developed for the detection of mixed pathogen infection in field samples.